The Impact of Weather on Attitudes and Repurchase Intention for Iced Tea in Semarang - Alfredo, Figo De; Martawijaya, Elang Ilik (LifeSciFi, 2025)
Repeat purchase intention is one of the most critical goals in marketing, especially among residents, where daytime temperatures tend to be relatively high. The habit of consuming cold beverages due to both necessity and the effects of weather also influences the shopping behavior. Iced tea is already a familiar product for the Indonesian population. The aim of this study is to examine the moderating role of weather on the effects of brand image, product quality, and price on consumer attitudes, as well as its impact on repeat purchase intention. This research employs a correlational design with a quantitative approach. A total of 120 respondents were sampled, and the collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that brand image, product quality, and price significantly affect consumer attitudes, which in turn influence repeat purchase intention. Furthermore, weather has a moderating effect on the influence of brand image and price on consumer attitudes. This study recommended that companies enhance brand image by incorporating customer ideas, implementing effective and conducive digital marketing strategies, and employing high-quality marketing packaging to generate a better perception of the product.